Surrogates Markers of Insulin Resistance - Hameed, Ekhlas Khalid; Al-Ameri, Laith Thamer (AL-Kindy College Medical Journal, 2022)
Insulin resistance is a fundamental feature of obesity, diabetes, and cardiovascular diseases and contributes to many of the metabolic syndrome's abnormalities. It is defined as a subnormal reaction to normal insulin concentrations or a situation in which greater than normal insulin concentrations are necessary for normal response.